Dating late Miocene marine incursions across Argentina and Uruguay with Sr-isotope stratigraphy - del Río, Claudia Julia (2018)
A Sr-isotope chronostratigraphy is presented for Miocene sediments deposited by the “Paranense” Sea along 1200 km of the southwestern Atlantic coast of Argentina and Uruguay. Numerical ages were obtained for shells of Aequipecten paranensis from the Argentinean Puerto Madryn Formation, Facies Balneario La Lobería, “Entrerriense Beds” of the Salado Basin, and Paraná Formation, and from the Camacho Formation (Uruguay). The 87Sr/86Sr ages fall into five age-groups that encompass the “Paranense” flooding in the latest Serravalian-Messinian interval. For the Puerto Madryn Formation, the ages span the latest Serravalian to the Tortonian and are stratigraphically coherent with the transgressive phase (11.9–10.4 Ma) and the regressive phase (10.2–9.82 Ma and 9.40–9.05 Ma) of that unit. Ages of 8.85–7.95 Ma for the “Entrerriense Beds” show them to be Tortonian while the Facies Balneario La Lobería, and the Paraná and Camacho formations span the age-range 7.50–6.00 Ma, comprising the Tortonian-Messinian interval. The regressive phase of the Puerto Madryn Formation, and the Facies Balneario La Lobería are respectively correlated with the basal and middle beds of the cliffs at Barranca Final, where the uppermost horizons of the Barranca Final Formation are exposed. The “Entrerriense Beds” are correlated with the “Cape Fairwheater Beds”. Dating the “Paranense” marine incursion permits a reappraisal of its paleogeography and differentiation of its deposits from those of the “Patagoniense” Sea. The flooding area was smaller than previously thought, with its northwestern-most boundary in the surroundings of the Santa Fe Province and its southernmost boundary in southern Santa Cruz Province. Moreover, the Paranaian Molluscan Bioprovince was coeval with the Valdesian Molluscan Bioprovince for 2.35 Ma and species included in the Aequipecten paranensis Zone lived for at least 5.90 Ma.